Determinants of Helminthic Infections and Anemia among Schoolchildren in Bahir Dar Zuria District, Northwest Ethiopia. (29th September 2021) - Fetene, Yeshimebet; Hailu, Tadesse; Yimer, Mulat; Alemu, Megbaru
Abstract : Background . Soil-transmitted helminths and Schistosoma mansoni are the major helminthic parasites that cause major public health problems among schoolchildren in developing countries. Infection with the above parasites decreases the hemoglobin level of children. However, information regarding the current status of helminthic infections and anemia is limited. Hence, this study aimed to assess the prevalence and determinants of helminthic infections and anemia among children. Methods . A cross-sectional study was conducted among 394 schoolchildren at Sekelet primary school in northwest Ethiopia, from February to March 2017. Study participants were selected by a systematic random sampling technique. Stool samples were collected and processed via the modified Ritchie's concentration technique to detect parasites in stool. A HemoCue Hb 201 analyzer was used to determine the hemoglobin level. Data were analyzed using SPSS version 23 statistical software. Association of helminthic infections and anemia with independent variables was determined using logistic regression analysis. Variables with P < 0.05 were considered statistically significant. Results . From the total of 394 participants, 185 (46.9%), 164 (41.6%), and 112 (28.4%) were infected with intestinal parasites, helminths, and STHs, respectively. The prevalence of hookworm and Schistosoma mansoni were 106 (25.6%) and 54 (13.7%), respectively. The prevalence of anemia among the schoolchildren was 278 (70.6%). Anemia was prevalent among 55 (51.9%) hookworm-infected and 19 (35.2%) S. mansoni -infected children. Not wearing shoes and improper utilization of latrine were significantly associated (P < 0.05 ) with hookworm infection, and frequent swimming in the river was also significantly associated (P ≤ 0.001 ) with Schistosoma mansoni infection. Schistosoma mansoni and hookworm infections were also significantly associated (P ≤ 0.001 ) with low levels of hemoglobin. Conclusion . Hookworm and Schistosoma mansoni infections and anemia are highly prevalent among schoolchildren. Hookworm and Schistosoma mansoni infections are significantly associated with anemia. Therefore, helminthic detection and hemoglobin determination should be done simultaneously among schoolchildren.